2007
DOI: 10.1007/s00421-007-0491-y
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory muscle fatigue impairs exercise performance

Abstract: High-intensity, exhaustive exercise may lead to inspiratory as well as expiratory muscle fatigue (EMF). Induction of inspiratory muscle fatigue (IMF) before exercise has been shown to impair subsequent exercise performance. The purpose of the present study was to determine whether induction of EMF also aVects subsequent exercise performance. Twelve healthy young men performed Wve 12-min running tests on a 400-m track on separate days: a preliminary trial, two trials after induction of EMF, and two trials witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…Prefatigue studies have shown either a significant decrease (69,79,132) or no change (24,113,118) in performance during subsequent heavy exercise. However, a problem with some of these studies is that respiratory muscle fatigue was not assessed (24,79,118) or was not quantified objectively using nerve stimulation techniques (69,132). Consequently, some of the studies may have failed to induce significant levels of respiratory muscle fatigue before subsequent exercise or overestimated the normally occurring level of fatigue in response to whole body exercise.…”
Section: Functional Consequences Of Respiratory Muscle Fatiguementioning
confidence: 99%
“…Prefatigue studies have shown either a significant decrease (69,79,132) or no change (24,113,118) in performance during subsequent heavy exercise. However, a problem with some of these studies is that respiratory muscle fatigue was not assessed (24,79,118) or was not quantified objectively using nerve stimulation techniques (69,132). Consequently, some of the studies may have failed to induce significant levels of respiratory muscle fatigue before subsequent exercise or overestimated the normally occurring level of fatigue in response to whole body exercise.…”
Section: Functional Consequences Of Respiratory Muscle Fatiguementioning
confidence: 99%
“…One approach to address this issue is to compare the whole body exercise responses between a fresh state and a fatigued state, when a certain group of muscles has been prefatigued. This particular approach has been used to highlight the contribution of respiratory muscle fatigue to exercise intolerance in healthy subjects (18,39,43). In this investigation, we planned to quantify the impact of preinduced quadriceps fatigue on a subsequent cycling exercise in healthy subjects and patients with COPD.…”
mentioning
confidence: 99%
“…The measurements were repeated 10 times. The three highest measurement values with an error of 5% or less were selected and the mean of the three values was calculated 7) . As measures of respiratory response, minute ventilation (V were measured using an exhaled gas analyzer (AE-300S, Minato, Osaka, Japan) on a breath-by-breath basis.…”
Section: Methodsmentioning
confidence: 99%